Nursing in Turkey. History, education, prospects - Nagórska, Małgorzata; Binkowska-Bury, Monika (Nursing Problems / Problemy Pielęgniarstwa, 2009)
Development of professional nursing in Turkey has started in the 19th century. Its coming into existence was greatly contributed to numerous wars in which Turkey was taking part that time. An important part in the process of nursing’s development should be attributed to the members of Red Crescent, who as the first organized courses for nurses. Those were the beginnings of nurses’ vocational training. The 20th century was the time of transformation and improving syllabuses for nurses, as well as, the beginnings of university education. Nowadays, Turkish nurses have achieved European standards of education and cooperate in professional and scientific areas with nurses worldwide.